2019
DOI: 10.1111/petr.13400
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after combined liver‐kidney transplantation: A longitudinal study of pediatric and adult patients

Abstract: It has been proposed that the liver protects the kidney in CLKT. However, few studies have examined long‐term renal function after CLKT and contrasted renal function of CLKT patients to KT patients beyond one year after transplantation. We studied long‐term renal function of CLKT patients and compared renal function of CLKT patients to KT patients between one and five years after transplantation. Patients who underwent CLKT between 1993 and 2011 were included (n = 34; 11 children and 23 adults). Ninety‐six (27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Despite the complex procedure and relatively small sample size, CLKT demonstrates excellent outcomes. A study by Kivela et al 11 reported a remarkable five-year overall survival rate of 91%. Similarly, de la Cerda et al 12 found a five-year kidney graft survival rate of 88%, higher than that of the isolated kidney transplantation (KT) group (72.0%).…”
Section: Outcomes Of Clktmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the complex procedure and relatively small sample size, CLKT demonstrates excellent outcomes. A study by Kivela et al 11 reported a remarkable five-year overall survival rate of 91%. Similarly, de la Cerda et al 12 found a five-year kidney graft survival rate of 88%, higher than that of the isolated kidney transplantation (KT) group (72.0%).…”
Section: Outcomes Of Clktmentioning
confidence: 97%
“…Despite the complex procedure and relatively small sample size, CLKT demonstrates excellent outcomes. A study by Kivela et al 11 . reported a remarkable five‐year overall survival rate of 91%.…”
Section: Current Status Of Clktmentioning
confidence: 98%
“…Due to the retrospective study design and the small numbers of patients we cannot answer questions regarding the frequency of rejection in comparison of isolated liver or kidney transplantation vs. CLKT. Data in adults and children have shown that the liver might "immunologically protect" the kidney after sequential and CLKT (32,33).…”
Section: Organ Function and Survivalmentioning
confidence: 99%
“…Of note, this final indication is much more commonly observed in adults rather than in children. 9 For the particular case of children with ARPKD, the indications for liver transplantation include the following: liver failure (with portal hypertension or without), recurrent cholangitis, cirrhosis (verified by biopsy), or "acute" mutations of polycystic kidney disease. 9,10 The ethical aspect of related organ donation remains controversial, especially in the case of multiorgan living donation.…”
Section: Introductionmentioning
confidence: 99%
“…9 For the particular case of children with ARPKD, the indications for liver transplantation include the following: liver failure (with portal hypertension or without), recurrent cholangitis, cirrhosis (verified by biopsy), or "acute" mutations of polycystic kidney disease. 9,10 The ethical aspect of related organ donation remains controversial, especially in the case of multiorgan living donation. 11 In pediatric practice, one of the parents of the recipient usually volunteers to become a living donor.…”
Section: Introductionmentioning
confidence: 99%